Measuring exposure to non-tuberculous mycobacteria: defining and testing novel antigens - Checkley, A; Anna Checkley (2012)
The tuberculosis (TB) vaccine bacillus bacillus Calmette-Guerin (BCG) has low efficacy against pulmonary TB in the tropics, where most TB disease occurs, and where an effective TB vaccine is most needed. It is possible that new TB vaccines in development may be similarly affected, in particular those based on the current BCG vaccine. There are several hypotheses to explain this phenomenon, one of which is that exposure to related non-tuberculous mycobacteria (NTM) reduces the efficacy of the BCG vaccine. Some animal data suggest that exposure to NTM results in reduced efficacy of BCG, although results from animal experiments are variable. Gamma interferon (IFN-g) responses to purified protein derivative (PPD) in humans also suggest that individuals living in regions where BCG has a low efficacy make robust immune responses to PPD suggestive of NTM exposure. The definition of antigens which are present in common NTM but absent from Mycobacterium tuberculosis (M. tuberculosis) and BCG would allow more detailed testing of this hypothesis. In this thesis, the definition and testing of such antigens are described. First, a bioinformatics pathway was used to define proteins which are present in common NTM and absent from the M. tuberculosis family (M. tuberculosis, BCG and other related mycobacteria). Following this, overlapping peptides from proteins selected during this process were tested in a mouse model of NTM infection, in humans from the UK and US who had NTM isolated from sputum samples, in healthy South Africans with known positive and negative responses to QuantiFERON®-TB Gold In-Tube test (Cellestis) and in cord blood samples. Low level but significant IFN-g responses were detected by ex vivo ELISpot in the healthy South Africans, and to the same peptide pools in individuals from the UK and US using a proliferation assay. No responses were detected in the cord blood cells, or in the mouse model. The implications of these findings, and the potential for further development of a test of NTM exposure, are discussed.